Dose-escalated icotinib in frail, older adults patients with EGFR-mutant lung adenocarcinoma: real-world efficacy and safety in a high-risk cohort - Wang, Junhui; Wang, Jian; Chen, Jianxin (Frontiers in Oncology, 2025)
BackgroundThe therapeutic potential of dose-escalated EGFR-TKIs in high-risk EGFR-mutant lung adenocarcinoma patients remains underexplored. This real-world study evaluated first-line double-dose icotinib (750 mg/day) in frail, older adults patients with poor performance status (ECOG PS 2).MethodsA single-center retrospective cohort analysis included 17 treatment-naïve patients with locally advanced/metastatic EGFR-mutant (ex19del/L858R) lung adenocarcinoma. All received icotinib 250 mg TID. Primary endpoints: objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and safety. Subgroup analyses assessed metastatic burden, mutation subtypes, and systemic inflammation biomarkers.ResultsThe study cohort, characterized by high-risk features including a median age of 73 years, poor performance status (ECOG PS 2 in 88.2% of patients), baseline brain metastases (41.2%), and multi-organ involvement (≥2 metastatic sites in 47.1%), demonstrated clinically significant antitumor activity. The objective response rate (ORR) was 52.9% (95% confidence interval [CI]: 27.8%–77.0%), while the disease control rate (DCR) reached 94.1% (95% CI: 71.3%–99.9%). Survival analyses revealed a median progression-free survival (PFS) of 14.6 months (95% CI: 2.63–26.58) and a median overall survival (OS) of 30.9 months (95% CI: 20.63–41.18). Notably, molecular stratification identified a significant survival advantage for EGFR L858R-mutant patients over those with exon 19 deletions (ex19del), with a hazard ratio (HR) for OS of 0.17 (95% CI: 0.05–0.65; p<0.01). Conversely, patients with ≥2 metastatic organs exhibited inferior PFS outcomes (HR = 3.18, 95% CI: 1.01–10.06; p=0.049). The safety profile remained favorable, with only one grade 3 rash (5.9%) reported among treatment-emergent adverse events, and no therapy discontinuations due to toxicity were observed throughout the study period.ConclusionDouble-dose icotinib shows robust efficacy and manageable toxicity in high-risk older adults patients, with clinically meaningful PFS/OS. The unexpected OS benefit in L858R mutants warrants validation but suggests a dose-dependent advantage. Metastatic burden remains a key prognostic factor. These findings support dose escalation as a viable strategy for frail populations with limited access to next-generation TKIs.